(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
The presence of Remorina albescens for the Colombian Caribbean is conrmed, based on a specimen of 165.91 mm of standard length collected in Nenguanje bay at the Tayrona National Natural Park. A taxonomic key for the remoras known from Colombian seas is also included.